Penerapan Konsep Solid Nature pada Penataan Ekowisata Mangrove di Gunung Anyar Surabaya (Program Studi Arsitektur Fakultas Teknik Universitas 17 Agustus 1945 Surabaya, 2022)
A mangrove forest is an ecosystem that mostly supports life in coastal areas. Its existence is very important because a mangrove forest has a great potential to support the economy, local societies, and environments. Far from the heart of town, there is a region that preserves the biological diversity that is located in Pantai Timur Surabaya in the form of a mangrove forest conservation site. One such example is “Wisata Anyar Mangrove” that was proposed to be the first Mangrove Great Park in Indonesia by the Surabayan Government. Nowadays, sadly we can see that its condition is miserable. Therefore reordering of the “Wisata Anyar Mangrove” to maintain it is a must to mend and improve the “Wisata Anyar Mangrove” area, considering the region will be developed into Mangrove Great Park as an continuous mangrove forest conservation endeavor.